2009
DOI: 10.1029/2009gl039533
|View full text |Cite
|
Sign up to set email alerts
|

Annual push moraines as climate proxy

Abstract: We reconstruct the terminus position of a mountain glacier in British Columbia, Canada from annual push moraines formed between 1959 and 2007. Our reconstruction represents the longest, annually‐resolved record of length change for a North American glacier. Comparison of annual recession with climate records indicates that glacier recession is controlled by air temperatures during the ablation season and accumulation season precipitation during the previous decade. Analysis among records of glacier frontal var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 33 publications
4
77
2
Order By: Relevance
“…Area changes are correlated with temperature anomalies lagged one to ten years and precipitation anomalies lagged six years. These values are comparable to other studies that have shown terminus changes responding to temperatures lagged a few years and precipitation lagged five to ten years (Salinger et al, 1983;Sigurdsson et al, 2007;Beedle et al, 2009). However, the rates of area change do not correlate with temperature and precipitation anomalies lagged the same number of years as area change.…”
Section: Area Change With Climatesupporting
confidence: 77%
See 1 more Smart Citation
“…Area changes are correlated with temperature anomalies lagged one to ten years and precipitation anomalies lagged six years. These values are comparable to other studies that have shown terminus changes responding to temperatures lagged a few years and precipitation lagged five to ten years (Salinger et al, 1983;Sigurdsson et al, 2007;Beedle et al, 2009). However, the rates of area change do not correlate with temperature and precipitation anomalies lagged the same number of years as area change.…”
Section: Area Change With Climatesupporting
confidence: 77%
“…I correlated lagged temperature and precipitation anomalies with glacier changes in the Columbia Icefield and found that annual and accumulation season precipitation anomalies have higher and more significant correlations than temperature anomalies. The higher correlations occurred at lag times similar to those reported by Salinger et al (1983), Sigurdsson et al (2007), and Beedle et al (2009). They determined that terminus changes are correlated with temperatures lagged a few years and precipitation lagged five to ten years.…”
Section: Climatesupporting
confidence: 67%
“…Terminus behavior at Illecilliwaet Glacier, in the Columbia Basin, was recorded since 1887 on a near-decadal basis, using photographs, field surveys and remotely sensed imagery (Champoux and Ommaney, 1986). Luckman et al (1987) Glacier was examined by dating annual push moraines (Beedle et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Third, the dynamical response of glaciers leaves footprints of past climate in their moraines (e.g. Beedle et al, 2009); they have hence become proven indicators of climate change. More importantly, the ice flow in valley glaciers and icefields comprises a high degree of complexity, primarily due to the irregular valley geometry.…”
Section: Introductionmentioning
confidence: 99%